Pengaruh Horizontal Mismatch terhadap Upah Tenaga Kerja di Indonesia - Yoselina, Aulia Indah; Marta, Joan; Dina, Rusy (Universitas Negeri Padang, 2024)
This study aims to examine the effect of horizontal mismatches on labor wages from various wage groups. This research uses a quantitative approach with secondary data from the 2020 BPS National Labor Force Survey. The method used is quantile regression by dividing wages into 5 quantiles (0.10, 0.25, 0.50, 0.75, and 0.90). The results show that horizontal mismatch at the D1-D3 education level has a negative and significant effect on labor wages at the middle and lower middle wage levels. This is because the ability to transfer knowledge from education and training of vocational graduates is limited. However, this is inversely proportional to the high wage level, horizontal mismatch has a positive and significant effect on labor wages. Meanwhile, horizontal mismatch at the D4-S3 education level has a positive and significant effect in all quantiles, this is because bachelor graduates have more job opportunities than vocational graduates.